2005
DOI: 10.5488/cmp.8.3.639
|View full text |Cite
|
Sign up to set email alerts
|

Polaron in a quasi 1D cylindrical quantum wire

Abstract: Polaron states in a quasi 1D cylindrical quantum wire with a parabolic confinement potential are investigated applying the Feynman variational principle. The effect of the wire radius on the polaron ground state energy level, the mass and the Fröhlich electron-phonon-coupling constant are obtained for the case of a quasi 1D cylindrical quantum wire. The effect of anisotropy of the structure on the polaron ground state energy level and the mass are also investigated.It is observed that as the wire radius tends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 40 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…In addition to theoretical and experimental methods, simulations in particular molecular dynamics and Monte Carlo simulations [66][67][68][69] together with model systems [70][71][72][73][74] are now widely used to unravel unsolved problems in condensed matter and complex systems physics [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. The reader will find details on our simulation procedure in previous papers [91][92][93], however for convenience we will resume it here.…”
Section: Calculationmentioning
confidence: 99%
“…In addition to theoretical and experimental methods, simulations in particular molecular dynamics and Monte Carlo simulations [66][67][68][69] together with model systems [70][71][72][73][74] are now widely used to unravel unsolved problems in condensed matter and complex systems physics [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. The reader will find details on our simulation procedure in previous papers [91][92][93], however for convenience we will resume it here.…”
Section: Calculationmentioning
confidence: 99%
“…Furthermore, most nanostructures are ionic crystals or polar materials, so the polarization effects have a great effect on their physical properties. [13] It can be predicted that the special geometry and size of QRs will lead to a stronger electron-phonon interaction and make the polaronic effect more obvious and interesting. Recently, Kovalev et al [14] studied the magneto polaron states of the particles in QRs by using a perturbation method.…”
mentioning
confidence: 99%
“…In the past, several workers [10][11][12][13][14][15] had carried out studies of the electron interaction with longitudinal optical (LO) phonons in quantum wires considering the modification of the electron energy spectrum and wave function due to their space localization but assuming the bulk forms for LO phonon modes. However, it was shown that the reduced sized scale and dimensionality have great influence leading to phonon confinement and changes in phonon modes [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%